Magnetic carbon nanotubes: a new tool for shepherding mesenchymal stem cells by magnetic fields. (January 2011) - Vittorio, Orazio; Quaranta, Paola; Raffa, Vittoria; Funel, Niccola; Campani, Daniela; Pelliccioni, Serena; Longoni, Biancamaria; Mosca, Franco; Pietrabissa, Andrea; Cuschieri, Alfred
Aims: We investigated the interaction between magnetic carbon nanotubes (CNTs) and mesenchymal stem cells (MSCs), and their ability to guide these intravenously injected cells in living rats by using an external magnetic field.Materials & methods: Multiwalled CNTs were used to treat MSCs derived from rat bone marrow. Cytotoxicity induced by nanotubes was studied using the WST-1 proliferation and Hoechest 33258 apoptosis assays. The effects of nanotubes on MSCs were evaluated by monitoring the effects on cellular growth rates, immunophenotyping and differentiation, and on the arrangement of cytosckeletal actin. MSCs loaded with nanotubes were injected in vivo in the portal vein of rats driving their localization in the liver by magnetic field. An histological analysis was performed on the liver, lungs and kidneys of all animals.Results: CNTs did not affect cell viability and their ability to differentiate in osteocytes and adipocytes. Both the CNTs and the magnetic field did not alter the cell growth rate, phenotype and cytoskeletal conformation. CNTs, when exposed to magnetic fields, are able to shepherd MSCs towards the magnetic source in vitro. Moreover, the application of a magnetic field alters the biodistribution of CNT-labelled MSCs after intravenous injection into rats, increasing the accumulation of cells into the target organ (liver).Conclusion: Multiwalled CNTs hold the potential for use as nanodevices to improve therapeutic protocols for transplantation and homing of stem cells in vivo. This could pave the way for the development of new strategies for the manipulation/guidance of MSCs in regenerative medicine and cell transplantation.